The human hand as an inspiration for robot hand development - Balasubramanian, Ravi; Santos, Veronica J. (Cham : Springer, 2014)
'The Human Hand as an Inspiration for Robot Hand Development' presents an edited collection of authoritative contributions in the area of robot hands. The results described in the volume are expected to lead to more robust, dependable, and inexpensive distributed systems such as those endowed with complex and advanced sensing, actuation, computation, and communication capabilities. The twenty-four chapters discuss the field of robotic grasping and manipulation viewed in light of the human hand's capabilities and push the state-of-the-art in robot hand design and control. Topics discussed include human hand biomechanics, neural control, sensory feedback and perception, and robotic grasp and manipulation. This book will be useful for researchers from diverse areas such as robotics, biomechanics, neuroscience, and anthropologists.
Constraints and Flexibility in Cortical Control of the Hand -- Synergistic Control of Hand Muscles Through Common Neural Input -- Transmission of Musculotendon Forces to the Index Finger -- The Control and Perception of Finger Forces.
Includes bibliographical references.
Keywords: Robot hands